Yeats and the logic of formalism - Bell, Vereen M., 1934- (University of Missouri Press, 2006)
"Attempts to balance traditional and modern criticism of Yeats by linking formalism and philosophy in the context of Yeats' work and evaluates its credibility in Yeats's practice in relation to other theoretical discourses and in the context of the turbulent cultural and historical circumstances under which Yeats worked"--Provided by publisher.